Immune thrombocytopenic purpura in adults in the last 10 years: single-centre experience - Pavkovic M; Trpkovska-Terzieva S; Sotirova T; Latifi A; Cevreska L; Stojanovic A (Македонска академија на науките и уметностите, Одделение за биолошки и медицински науки = Macedonian Academy of Sciences and Arts, Section of Biological and Medical Sciences, 2012)
Abstract Background: Immune thrombocytopenic purpura (ITP) is a benign disease with low morbidity and mortality and frequent remissions that occur spontaneously or in response to first-line treatment with steroids or splenectomy. Aim: The purpose of this study is to describe the clinical outcomes of 170 patients with ITP diagnosed and/or treated in our hospital between 2000 and 2010. Methods and results: The median age at diagnosis was 47 years. Forty three (25%) were asymptomatic, 65% had minor skin or mucosal bleeding and 10% had significant bleeding from the gastrointestinal or genitourinary system. The median platelet count at diagnosis was 13x10(9)/L (range: 0-98x10(9)/L). Median follow-up of all patients was 13 months. Ninety-five patients had a follow-up longer than 12 months, with median 44 months (range 14-384). Corticosteroids were the initial treatment for 161/170 (95%) patients, 38 (22%) were splenectomized, 25 (14.7%) were treated with intravenous gamma globulins, while 9 did not received any specific treatment. A complete response to initial treatment (prednisone±splenectomy) was achieved in 55/161 (34.2%), a partial response in 90 (55.9%) and no response in 16 (9.9%) patients. In the group of patients with follow-up longer than 1 year; 28 (29%) patients had refractory or unresponsive ITP with a median follow-up of 66 months. All patients with refractory ITP were treated with steroids, 11 were splenctomized, significantly more patients with refractory ITP 12 (43%) were treated with IVIG compared with other ITP patients (16%), p=0.005. The median age of 38 splenectomized patients was 28 years and it is significantly different from the other patients (p<0.001). There were no significant differences in other characteristics between splenctomized or refractory ITP and other patients at diagnosis. Conclusion: Our results were similar to results already reported in other similar studies.